Effects of colloidal complexes formation between resveratrol and deamidated gliadin on the bioaccessibility and lipid oxidative stability. (August 2017) - Qiu, Chaoying; Wang, Bin; Wang, Yong; Teng, Yinglai
Abstract: Deamidated wheat gliadin (gliadin) and its conjugates were applied to form complexes with resveratrol (Res). Res is a kind of polyphenol known for its low bioavailability and solubility in aqueous solution. The morphology of the complexes and Res stability were compared. Colloidal complexes were incorporated into emulsion to evaluate antioxidant activity. Results indicated that both gliadin and glycosylated gliadin can form nanocomplexes with Res and had high retention efficiency. Colloidal complexes solution can efficiently protect Res from UV-light transformation and the content of trans -Res was significantly improved ( p < 0.05). Higher Res bioaccessibility in the complexes after digestion indicated that colloidal complexes can efficiently increase Res stability during gastrointestinal digestion. Dextran moieties were more efficient to enhance Res bioaccessibility due to steric hindrance. In the emulsion system, the colloidal complexes can significantly lower lipid oxidation evaluated by lipid hydroperoxides and hexanal generation during storage. The emulsifying properties of protein promoted the accumulation of Res at the oil-water surface. Therefore, it can act as an antioxidant to inhibit lipid oxidation. These results proved that the gliadin based delivery system is efficient to incorporate bioactive compounds in food beverages and emulsions. Graphical abstract: Highlights: Gliadin and its conjugates were applied to form colloidal complexes with Resveratrol. Nanocomplexes formation could protect Res from UV-light transformation. Res stability was efficiently improved in nanocomplexes during in vitro digestion. Dextran moieties on protein enhanced Res bioaccessibility due to steric hindrance. Protein-Res complexes could significantly lower lipid oxidation in emulsion.